Growing Babies, Growing faith: The Formation of Faith in The Life of the Child - Price, Yusra (School of African and GenderStuds, Anth and Ling, 2022)
The composition and formation of a young child's Muslim identity is situated within a contextual landscape of location, history, demographic, family, community and more which makes every child's upbringing unique. Through multiple interviews, visits and general discussions, this research sets out to understand how caregivers located in Cape Town conceptualise their world, make sense of incorporating religious practice and values into their children's daily lives, and how this is balanced with caregivers' perceptions of what a child can handle at two years old. From our interviews, three themes emerged: firstly, the histories, values and practices of caregivers shape the contextual environment of their children's religious upbringing. Secondly, in addition to Islamic education and practice, a child's feelings and emotions must be nurtured to foreground a positive association with and devotion to Islam. Lastly, notions of time demarcate and shape how caregivers temporalize their child-rearing practices. The aim of this research is to contribute towards the growing discourses around childhood and religion through an ethnography of child-rearing in Cape Town.